(3JPcQI GdYGQajf hJHUQI GdeSJHUQjfs - (3HgGA GdOjf CHh GdaJM eMeO Hf CMeO Hf efUhQ GdCHTjgj, GdCHTjgj,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3BNQgG (B:s
(3Je GdcJGH GdeHGQc hfLR hGdMeO ddg QH GdYGdejf s
(3GdhQbI GdChdi hHYV GdhQbGJ SjFI GdJUhjQs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B229 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B110s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs